La clase multiserial de educación del campo, en Pau dos Ferros RN - Bem, Geralda Maria de; Silva, Cicero Nilton Moreira da (Revista Hipótese, 2019)
This paper aims at reflecting about the national politicy of Countryside Education in Brazil and its refutation in the proportion of countryside teaching in Pau dos Ferros; to study the teaching-learning process and to inquire the pedagogical proposals of the schools with multi-series classrooms in this countryside. We used, as methodological procedure, field research, carried out on semester 2014.1, in two schools of the countryside of Pau dos Ferros-RN: It is worthwhile to point out that this research is a qualitative one. The research pointed out that the teachers face difficulties to teach in this modality of teaching, which highlighted, as main problems, the distancing within the pedagogical team, the absence of the pedagogical policy project and a curriculum that is appropriate to the specificities of the countryside teaching.
Keywords: Clases Multiserias; Educación del Campo; Educación